Addressing Violence Against Women and Children Through the 'Lapor Pak 129' Innovation - Pusparini, Rani (Journal of Governance and Administrative Reform, 2024)
Abstract This study aims to elucidate the service innovations implemented by the Office of Women's Empowerment and Child Protection and Population of the East Java Provincial Government to provide protection against violence towards women through the LAPOR PAK 129 innovation. The number of complaints of violence against women and children is quite high. Therefore, the Office of Women's Empowerment and Child Protection and Population of East Java Province developed this innovation to address the issue. It serves not only as a platform for receiving complaints of violence against children and women but also provides health services, social rehabilitation services, legal aid and enforcement services, as well as repatriation and social reintegration services. This study employs a qualitative method. Data collection techniques include interviews, observations, and document studies. This study applies interactive data analysis. The results of the "LAPOR PAK 129" innovation by DP3AK East Java aim to provide protection and services to women and children from violence through a toll-free telephone service and updated complaint procedures. This innovation encompasses non-discriminatory policies, active participation of children in recovery, and a new governance system, thereby enhancing the ease, convenience, and effectiveness of services. Keywords: innovation, service, violence, women and children.   Abstrak  Penelitian ini bertujuan menjelaskan inovasi pelayanan yang dijalankan oleh Dinas Pemberdayaan Perempuan dan Perlindungan Anak dan Kependudukan (DP3AK) Pemerintah Provinsi Jawa Timur dalam memberikan perlindungan terhadap kekerasan perempuaan melalui inovasi LAPOR PAK 129. Pengaduan kekerasan Perempuan dan anak cukup tinggi. Oleh karena itu, Dinas Pemberdayaan Perempuan dan Perlindungan Anak dan Kependudukan Provinsi Jawa Timur membuat inovasi untuk menangani permasalahan tersebut. Tidak hanya sebagai tempat dalam menerima pengaduan kekerasan terhadap anak dan Perempuan saja, tetapi memberikan layanan kesehatan, layanan rehabilitasi sosial, layanan bantuan dan penegak hukum, hingga layanan pemulangan dan reintegrasi sosial. Penelitian ini menggunakan metode kualitatif. Teknik pengumpulan data dilakukan dengan cara wawancara, observasi dan studi dokumentasi. Penelitian ini menerapkan analisis data interaktif. Hasil penelitian Inovasi "LAPOR PAK 129" oleh DP3AK Jawa Timur bertujuan untuk memberikan perlindungan dan pelayanan kepada perempuan dan anak dari kekerasan melalui layanan telepon bebas pulsa dan pembaruan prosedur pengaduan. Inovasi ini mencakup kebijakan nondiskriminasi, partisipasi aktif anak dalam pemulihan, serta sistem tata kelola baru, sehingga meningkatkan kemudahan, kenyamanan, dan efektivitas pelayanan. Kata kunci: inovasi, pelayanan, kekerasan, perempuan dan anak.